Unraveling the Role of the Apical Papilla During Dental Root Maturation - Driesen, Ronald B.; Gervois, Pascal; Vangansewinkel, Tim; Lambrichts, Ivo (Frontiers in Cell and Developmental Biology, 2021)
The apical papilla is a stem cell rich tissue located at the base of the developing dental root and is responsible for the progressive elongation and maturation of the root. The multipotent stem cells of the apical papilla (SCAP) are extensively studied in cell culture since they demonstrate a high capacity for osteogenic, adipogenic and chondrogenic differentiation and are thus an attractive stem cell source for stem cell-based therapies. Currently, only few studies are dedicated to determining the role of the apical papilla in dental root development. In this review, we will focus on the architecture of the apical papilla and describe the specific SCAP signaling pathways involved in root maturation. Furthermore, we will explore the heterogeneity of the SCAP phenotype within the tissue and determine their micro-environmental interaction. Understanding the mechanism of postnatal dental root growth could further aid in developing novel strategies in dental root regeneration.